An Empirical Study on Metropolitan Cebu Residents' Online Buying Behavior during the Community Quarantine Period - Joemariz Abella; Rodney Rabe; Antoniette Almaden (Philippine Association of Institutions for Research, Inc., 2021)
Online Shopping platforms have prompted vital changes in several aspects of the digital market, yet the reasons why consumers buy online are still not clear. Driven by technological advancements and evolving consumer demand, online shopping has been remodeled through various e-commerce platforms that were progressing even before the coronavirus pandemic began. The study examined the consumers' behavior whether there were significant changes in the Metropolitan Cebu residents' online shopping behavior within the context of the community quarantine period. Descriptive method and convenience sampling technique were used to determine the determinants of the 543 randomly selected participants' consumer behavior, online shopping perception, and online purchasing challenges experienced during the quarantine. The selected factors to be explored are personal, social, psychological, cultural, and how they affect consumer behavior towards online shopping. Based on the aforementioned examines, it has been found out that almost 20.1 percent of the respondents had not changed their online shopping habits since the quarantine began. Around 59.5 percent increased their spending online, and 20.4 percent of the respondents have decreased their online spending during the quarantine. As Metropolitan Cebu has already transitioned to the MGCQ phase, 71.3% of the respondents were expected to continue their online shopping activity to a more sustainable and conscious online product spending after the coronavirus pandemic.